Neologisms in Publicistic Discourse of Foreign Language: Methods of Teaching (Based on Italian and French Languages) - M. G. Yashina; N. V. Polyakova (Научный диалог, 2017)
The study focuses on such linguistic phenomena as neologisms in business discourse of the French and Italian languages. The problem faced by the authors is how to teach language learners to recognize and understand the neologisms that are so often encountered in the business press? The relevance of this topic is determined by the necessity of understanding the neologisms as a widespread phenomenon in any living language. The authors believe that the neologisms are the characteristic of the language of journalism, which is committed to the brightness and imagery. It is emphasized that learners of a foreign language consider the neologisms as difficulty even at an advanced stage of training. The characteristic is given of ways of forming the new words: semantic derivation, diversity method, etc. Material is studied in the comparative aspect. For example, the authors draw attention to the fact that in the Italian language the tendency of formation of new words from proper names is expressed more clearly than in the French. Methodological principles of work with neologisms when learning a foreign language are listed.